Oral cancer from a health promotion perspective: experience of a diagnosis network in Ceará - SOUSA,Fabrício Bitu (2014)
The aim of this study is to share the experience of implementing a network for the diagnosis of oral cancer by integrating primary, secondary, and tertiary oral health care centers and identifying the possible weaknesses of the process. The study also investigated the risks of exposure to the main risk factors for oral and lip cancer and their most common potentially malignant lesions (PML). A quantitative cross-sectional study was conducted in two different regions, with patients seen at a primary health care facility from August 2010 to July 2011. Patients with oral lesions were referred to dental specialty centers for biopsy. Patients with PML were treated in dental specialty centers, and patients with squamous cell carcinoma (SCC) were referred to tertiary health care facilities. The dentists' knowledge of PML and SCC was assessed by an objective questionnaire. A total of 3,965 individuals were examined, 296 lesions were found, and 73 biopsies were performed, of which 13.7% were diagnosed as PML and 9.6% as SCC. Tobacco use and sunlight exposure were associated with SCC (85.7%) and PML (80%), respectively. In total, 55 dentists were assessed. The lesions most commonly recognized as PML were leukoplakia (74%), erythroplakia (57%), and actinic cheilosis (56%). Most dentists (74%) felt incapable of performing biopsies, most likely because of an anxiety towards oral cancer, and 57% had never performed one. The integration of primary and secondary health care enables the diagnosis of PML and SCC and establishes a diagnosis network. However, the inability of most primary care dentists to identify PML and perform biopsies is a weakness of the diagnostic process.